Novel surfactant-free waterborne acrylic-silicone modified alkyd hybrid resin coatings containing nano-silica for the corrosion protection of carbon steel. Issue 8 (24th May 2019) - Zhong, Shenjie; Li, Jiawei; Cai, Ying; Yi, Lingmin
ABSTRACT: We report a novel waterborne acrylic-silicone modified alkyd nanocomposite latex containing nano-silica prepared by the surfactant-free miniemulsion polymerization. The influences of γ-methacryloxy-propyltrimethoxysilane- (MPS-) modified nano-silica particle contents to the thermal, mechanical and anti-corrosion performance of hybrid latex coatings were studied. The results revealed that the incorporation of nano-silica particles into latex films could directly increase the thermal stability and mechanical properties. Electrochemical corrosion studies revealed that these nanocomposite coatings exhibited superior corrosion resistance performance (inhibition efficiency 99.36% and corrosion rate 1.09 × 10 −3 mm per year) than that of the control system (without SiO2 NPs). GRAPHICAL ABSTRACT: